Développement professionnel et paliers de professionnalité : le cas de la formation des professeurs stagiaires en Education Physique et Sportive - Florian Ouitre (Nantes Université, 2011)
This article reports on the results of a study aimed at measuring and understanding the impact of a training project on the development of the professional skills of trainee teachers currently undergoing professional training (Professeurs de Lycée et de Collège specializing in Physical and Sport Education in the second year of IUFM (University Institutes of Master Training= Teacher Training). The training project rises from the conception of how the didactic system works, which is viewed here as the conceptual frame of this study. There are three main classes of professional problems that trainee teachers have to identify, prior to analysing them in order to progressively envisaging possible solutions for dealing with them. This work is an attempt to understand the professional practices of the trainees who are the object of the study. Here it is a matter of going beyond the observed appearances of the practice in order to gain an insight into the reasoning of the actors displaying such practices. The thinking thus exposed seems to have a certain permanence during the course of the year of training. The data we collected in this study come from the reports we wrote after the visits we made during this training year and the preparatory documents provided by the students themselves. We also used the interviews we had at the end of the training period in order to collect the actor's point of view. Apart from the different forms these practices can take, (varied teaching activities in differents contexts), we endeavoured to bring out the logic behind these practices. What we discovered shows a certain permanency throughout the training year among the trainees. This permanency can be seen in the structure of the observed practices. This permanence is expressed through the structure of the observed practices. It is also expressed from the point of view of their occurrence in the training year. These thought processes link up to what are effectively modes of operation, to which we assign the status of foundations of professionalism. At. the end of our study, we have come to the conclusion that the four foundations of professionalism correspond to the four modes of operation of the didactic system. We describe them in the following and outline a number of approaches that could be used to extend the concept of foundation of professionalism.